Local scour downstream of weir - Ang, Boon Chuang (2015)
Scour in the sediment bed downstream of a weir is an unfavourable process which can undermine the weir structure. This project aims to investigate the scouring phenomenon downstream of an overflowing weir and how the scouring effect can be reduced. Furthermore, the effect of an apron length will also be studied. Experiments were conducted on an 8.0m by 0.3m wide by 0.6m deep flume with five different flowrates and three different tailwater depths in these runs. The results showed that the scour parameters can be reduced by decreasing the flowrate, increasing the tailwater depth and increasing the apron length. Combining results from previous studies also showed that an increase in the median sediment size also decreases the scour depth. Using the “Predetermined” method, the equilibrium scour time and maximum equilibrium scour depth of the experimental runs can be determined for further analysis. Empirical equations with different variables are then proposed using dimensional and regression analysis on the data collected in this study and other studies to predict the equilibrium scour time and maximum equilibrium scour depth.